2013
DOI: 10.1039/c3cp53671h
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the supramolecular interactions involving tris-dipicolinate lanthanide complexes in protein crystals by a combined biostructural, computational and NMR study

Abstract: Incorporating in a non-covalent manner lanthanide derivatives into protein crystals has shown to be of prime interest for X-ray crystallography, insofar as these versatile compounds can co-crystallize with proteins through supramolecular interactions, in addition to being strong anomalous scatterers for anomalous-based diffraction techniques. In this paper, the selective affinity of tris-dipicolinate lanthanide complexes for cationic amino-acid residues is explored, using a panel of experimental (X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 66 publications
(74 reference statements)
0
20
2
Order By: Relevance
“…[16] This interaction was simulated with small molecular models and the stabilization energy of this strong H-bond was estimated by density functional theory (DFT) calculations to around À10 kcal mol À1 . [17] In view of the unique properties of the Crystallophore with both nucleating and phasing capabilities, unravelingi ts interactions with proteins is of prime importance for future developments. For instance, such knowledge will allow to anticipate Crystallophore effects on new protein targets, based on their amino acids sequence, top recisely define crystallization conditions optimizing the protein-Crystallophore interactions and for the design of the next Crystallophore generations with improvedp roperties.H erein, we describe the main structural features of six structures of four proteins co-crystallized with Tb-Xo4.…”
mentioning
confidence: 99%
“…[16] This interaction was simulated with small molecular models and the stabilization energy of this strong H-bond was estimated by density functional theory (DFT) calculations to around À10 kcal mol À1 . [17] In view of the unique properties of the Crystallophore with both nucleating and phasing capabilities, unravelingi ts interactions with proteins is of prime importance for future developments. For instance, such knowledge will allow to anticipate Crystallophore effects on new protein targets, based on their amino acids sequence, top recisely define crystallization conditions optimizing the protein-Crystallophore interactions and for the design of the next Crystallophore generations with improvedp roperties.H erein, we describe the main structural features of six structures of four proteins co-crystallized with Tb-Xo4.…”
mentioning
confidence: 99%
“…The positively charged arginines ide chains play ac ritical role in [Ln(DPA) 3 ] 3À association to the protein. [42][43][44][45][46][47][48][49] In the crystal structure of the HEWL-[Eu(DPA) 3 ] 3À complex, [42] the electrostatic interaction between [Gd(DPA) 3 ] 3À and Arg124a tbinding site 1i st he major driving force for ligand association; complexation is accompanied by the disappearance of the methyl signals of the Ala10 and Leu129 residues in the 13 C-HSQC NMR spectra.F urthermore, the interaction of [Gd(DPA) 3 ] 3À and Arg128a tb inding site 2r esulted in the disappearanceo ft he Leu129 signal in the 13 C-HSQCN MR spectra. The broadened signalo bserved fort he methyl groups of residue Leu75 could be attributed to binding site 3, which contains Arg74.I ti sn otable that binding site 3i nt he crystal structure of the HEWL-[Eu(DPA) 3 ] 3À complex overlaps with the substrate binding pocket of HEWL (PDB ID:2 LVB).…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] Recent studies showed that the positivelyc harged arginine side chains of HEWL interact with negativelyc harged lanthanide complexes [Ln(DPA) 3 ] 3À (DPA = dipicolinic acid). [42][43][44][45] The reported crystal structure of aH EWL-[Eu(DPA) 3 ] 3À complex indicated that five [Eu(DPA) 3 ] 3À moleculesa re bound to one HEWL protein at five differents ites. [42] The electrostatic interactions between the negativelyc harged [Eu(DPA) 3 ] 3À speciesa nd positivelyc harged arginineside chains, as well as hydrogen bonding between the ligandsa nd protein,p rovide an excellent structuralm odel to address the critical issues (e.g.,d ynamics, flexibility,a nd binding strength of each individual binding site) involved in molecular recognition between ap rotein and ligand in am ultisite interacting system.…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables various and multiple supramolecular interactions with protein residues that diversify the possible binding sites with good occupancies. The design of the crystallophore followed the same philosophy and has benefited from our past experience of deciphering the mode of interactions of lanthanide complexes at the protein's surface (Girard et al, 2002;Dumont et al, 2013;Stelter et al, 2014).…”
Section: Tb-xo4 Is a Powerful Phasing Agentmentioning
confidence: 99%